Omentoplasty to assist perineal defect closure following laparoscopic abdominoperineal resection. (24th October 2013) - Killeen, S.; Mannion, M.; Devaney, A.; Winter, D. C.
Abstract: Aim: This technical note describes laparoscopic production of a well vascularized, omental flap of adequate size to fill the pelvic floor defect in the course of laparoscopic abdominoperineal resection (LAPR). Method: The omentum is laparoscopically mobilized and transposed to the pelvis following full LAPR in three discrete stages. Results: Laparoscopic omental mobilization, transfer and buttressing of a primary perineal repair reduces pelvic dead space and facilitates closure following LAPR with minimal additional operative time or complications and a potential reduction in perineal wound associated morbidity. Conclusion: Laparoscopic omental mobilization is technically feasible and provides a safe method to aid perineal wound closure.